The clinical significance of simultaneous detection of pathogens from bronchoalveolar lavage fluid and blood samples by metagenomic next-generation sequencing in patients with severe pneumonia. Issue 1 (24th January 2021) - Chen, Jinlian; Zhao, Yuxi; Shang, Yongpeng; Lin, Zhiwei; Xu, Guangjian; Bai, Bing; Zheng, Jinxin; Li, Peiyu; Mao, Yuanchen; Deng, Qiwen; Yu, Zhijian
Abstract : Introduction. Bloodstream infection is a common complication in patients with severe pneumonia and is regarded as an independent risk factor for prediction of poor outcome. Metagenomic next-generation sequencing (mNGS) has been widely applied for pathogen determination of various clinical specimens from patients with infectious diseases. However, the clinical significance of and necessity for simultaneous pathogen detection of both blood samples and bronchoalveolar lavage fluid (BALF) by mNGS in patients with severe pneumonia remains unclear. Hypothesis/Gap Statement . Simultaneous detection of pathogens from both BALF and blood samples in patients with severe pneumonia helps to determine the complication of the bloodstream infection. Aims. This study aimed to elucidate the clinical significance and necessity of pathogen detection simultaneously in both blood samples and BALF samples with the application of mNGS in patients with severe pneumonia. Methods. In this study, 20 patients with severe pneumonia were enrolled and the potential pathogens in both BALF and blood samples were detected simultaneously by conventional microbial examination and mNGS tests. Moreover, multiple consecutive microbial detections were undertaken to investigate the dynamic variation of pathogens during the course of disease progression in two of the 20 patients. Results. In 85 % (17/20) of the patients with severe pneumonia, various pathogens were determined positively in the BALF by mNGS, including 10 cases with bacterial infection, five cases with viral infection and two cases with fungal infection. By contrast, pathogens in 50 % (10/20) of cases could be detected positively in the BALF by conventional microbial tests. Among 17 severe pneumonia patients with mNGS-positive BALF, pathogens were also identified in 10 cases with mNGS-positive blood samples. By contrast, only one patient complicated with a bloodstream infection could be found by conventional bacterial culture. Moreover, the pathogens from BALF were highly consistent with that from blood samples detected by mNGS in the early stage of the disease. With disease progression and after recurrent antibiotic treatment, significant dynamic changes of the microbial species from the BALF and blood samples could be clearly found by mNGS. Conclusions. This study emphasizes the utility of mNGS in the rapid simultaneous detection of pathogens from both BALF and blood samples in patients with severe pneumonia, and could allow determination of bloodstream infection and guide clinicians regarding antimicrobial treatments.